Religion and Social Control in Nigeria:The Rise and Rise of Secularization and Fanaticism (2015)
Religion as well as its institutions in every society has always played a pivotal role in the maintenance of social order and control, as well as fostered social change, disorder, deviance, social death and re-birth. this paper focuses on the dynamic nature of the relationship between religion and social control; it argues that whilst religion might be functional, many a part of it is not, especially taking into consideration the issues of religious violence, and other critical social issues. It further discusses the rise of secularization and fanaticism as two polar ends in the religious discourse while advancing its explanation for the topsy-turvy relationship between religion (and its constituent phenomena of secularization and fanaticism) and social control particularly in the light of the Nigerian social situation. It concludes that the influence of religion rather than waning has increased, alongside its secularization and fanaticism.